Effect of the Topical form of Achillea millefoliumon on Nipple Fissure in Breastfeeding Women: A Randomized Controlled Clinical Trial - Sara Abdoli; Ensiyeh Jenabi; Seyedeh Zahra Masoumi; Farideh Kazemi; Shirin Moradkhani (Iranian Journal of Neonatology, 2020)
Background: Nipple fissure is one of the most common diseases in breastfeeding which leads to maternal pain and disruption of the mother-infant relationship. Since the most important consequence of nipple fissure is the deprivation of the infant from breast milk, it is very important to prevent and treat this condition. The aim of this study was to investigate the effect of the topical form of Achillea millefoliumon on nipple fissure in breastfeeding women referring to the comprehensive health centers of Hamadan, Iran. Methods: This study was a randomized double-blind clinical trial that was conducted in Hamadan comprehensive health centers in 2018. Treatment methods were taught by the researcher to 80 eligible breastfeeding women who were randomly divided into two groups of 40 subjects. After breastfeeding, the intervention group covered their own nipples with a tea bag of Achillea millefolium, while the control group applied some of their own hindmilk on their nipple. These interventions were performed at least 4 times a day for 14 days. Checklists of store fissure scale, visual analog scale, and midwifery and demographic characteristic questionnaire were completed in both groups before the treatment and 4, 8, and 14 days after starting the treatment. The data were analyzed using SPSS software (version 16). Results: The results showed that the intensity of fissure and the mean pain score in the two groups were not statistically significant in the pre-intervention phase. However, the scores of the intensity of fissure and pain in the Achillea millefolium group were lower than those in the breast milk group on days 4, 8, and 14 after the intervention, and these differences were statistically significant (P<0.001). Conclusion: The results of this study showed that the topical form of Achillea millefolium was more effective than breast milk in treating nipple pain and fissure.